Multifunctionality of the [C2mim][Ln(fod)4] series (Ln = Nd-Tm except Pm): magnetic, luminescence and thermochemical studies - Cerdeira, Ana C.; Leal, Joao P.; Avo, Joao; Viola, Catarina; Casimiro, Maria H.; Ferreira, Luis M.; Paz, Filipe A. A.; Pereira, Laura C. J.; Pereira, Claudia C. L.; Monteiro, Bernardo (New journal of chemistry, 2022)
A series of nine tetrakis lanthanide beta-diketonate complexes of the type [C(2)mim][Ln(fod)(4)] (C(2)mim = 1-ethyl-3-methylimidazolium, fod = 6,6,7,7,8,8,8-heptafluoro-2,2-dimethyl-3,5-octanedionate) were prepared, with yields above 80%, and their thermochemical, photophysical and magnetic susceptibilities were evaluated. Thermochemical studies presented a rare and reversible conversion between two solid phases (polymorphism), characteristic of the [Ln(fod)(4)](-) anion. Photophysical and magnetic studies revealed that Dy and Er presented the multifunctionality of being simultaneously SMMs and visible (Dy) or near infra-red (Er) emitters. The Nd, Ho and Tm analogues present characteristic emission bands in the NIR region (800-1200 nm), while Sm, Eu, Tb and Dy present emissions in the visible range. Magnetic susceptibility of Tb, Dy, Ho, Er and Tm salts were measured in the temperature range of 2-300 K, showing paramagnetic behaviour, although with different regimes, with AC susceptibility measurements, at different frequencies in the range of 10-10 000 Hz, providing evidence of slow magnetic relaxation processes for Gd, Dy and Er analogues with SMM behavior.